PENJAMINAN MUTU PENDIDIKAN TINGGI - Alawiyah, Faridah (Jurnal Aspirasi, 2011)
One of the most urgent issue in the development of Indonesia today is the quality of human resources, mainly generated by higher education which is the source of innovation and solutions for the growth and development of the nation. This paper description how quality assurance has been regulated in Indonesia trough the Sistem Pendidikan Nasional laws. But the direction and coordination of higher education quality assurance system is stil uncleared, so that the quality of higher education is not yet guaranteed. Therefore, a grand design of quality assurance systems should be made to solve the problem of the low quality of higher education in Indonesia.